Providentia, pneumatologie en praktijken: Over de voorzienigheidsleer en menselijke praktijken in de context van het immanente kader - Gooijer, Aaldert (Kerk en theologie, 2026)
In theology, providence is often linked to the Father, the Creator of heaven and earth. However, recent literature advocates a Trinitarian reflection on the doctrine providence. This article aims to contribute to this, focusing on the work of the Spirit and human practices. Following Kelsey, the author argues that the Spirit is active in and through human practices. This leads to a new reflection on the three aspects of providence: Conservation, Concurrence, and Government.